THE ANALYSIS OF THE IMPLEMENTATION OF BUSINESS ETHICS PRINCIPLES AT UD. CHICKEN CUT YA2N. S - Elen Sari (STIA Bagasasi, 2023)
Business is a profit-seeking activity, a lot of fraud occurs just to seek personal gain without paying attention to applicable business ethics. This study aims to analyze the implementation of the principles of business ethics in the business activities of UD. Ayam Goreng Ya2N.S. This study uses descriptive qualitative methods with data collection techniques in the form of interviews and documentation. The primary data in this research are the owner (owner) of UD. Ya2N.S Broiler Chicken and consumers who buy chicken at the Ya2 N.S kiosk. The results of the study show that UD. Ya2N.S's Cut Chicken has implemented the principles of business ethics well in its business activities, with the principles of autonomy, the principles of honesty, the principles of fairness, the principles of mutual benefit and the principles of moral integrity. The implementation of the principles of business ethics results in the maintenance of good relations with consumers and other stakeholders.